Developments in chiral counterion-directed asymmetric reactions - Cavell, A (2016)
The research outlined herein consists of two projects, each relating to the investigation and development of asymmetric phase-transfer catalysed reactions. The aim of the first project was to develop a two-component cascade reaction that would assemble the valuable pyrroloindoline framework from simple and readily available starting materials, namely an isocyanide-containing substrate and a Michael acceptor. Successfully, we were able to synthesise a variety of pyrroloindolines containing up to three stereocentres with excellent diastereo- and enantioselectivity. This rapid strategy uses a chiral ammonium salt to control the selectivity and exploits the remarkable reactivity profile of acidic isocyanides. A mechanistic proposal involving hydrogen-bond activation of the isocyanide is described, originating from the specific design of the Michael acceptor component. Meanwhile, the objective of the second project was to develop a desymmetrising SN2 reaction on achiral biaryl substrates under asymmetric phase-transfer conditions, offering a new pathway to axially chiral biaryls. We were able to generate such products, which can be subsequently derivatised, with tremendous enantioselectivity and pleasing diastereoselectivity, particularly when using a glycine Schiff base as the nucleophile.